O processo coletivo de elaboração das Diretrizes Curriculares para a educação básica do Paraná e a inserção das geometrias não euclidianas - Caldatto, Marlova Estela (2011)
The process of development of Curriculum Guidelines for Elementary School - Mathematics - is regarded by the Paraná Ministry of Education as being a collective elaboration procedure, occurring inside the schools of Paraná with the active participation of all teachers working in state schools. The goal of this research is to present a historical review of the elaboration of these guidelines, based on the recollections of teachers who were present during the process. The focus of the study is on the incorporation, in the framework of contents to be taught in elementary school, of the Non-Euclidean Geometry. Due to the poor training of teachers in what concerns the Euclidean geometry and, inevitably, the problems involved in teaching this subject in elementary school, our interest has been aimed at understanding how and why this incorporation occurred, how the teachers taking part in the preparation of the guidelines see this event and, considering the decisions taken during the process, what their contribution was. The information collected were acquired through the analysis of documents developed by the State Ministry of Education, research papers related to this subject and by interviewing 15 teachers who, somehow, were involved in the process. 9 teachers from the Maringá Regional Education centre, 5 teachers members of the mathematics technical team of the State Ministry during the preparation of the guidelines and a critical reader of the mathematics discipline were interviewed. In order to examine and analyse the interviews properly the method of Oral History Theme was chosen. The outcomes of our research showed that the elaboration process of the guidelines was much more influenced by management issues and internal crises which happened in the Ministry than by the participation of the professionals from state schools, and that the decision to insert the Non-Euclidean geometries did not come from any of these teachers, but was undertaken through a maneuver of the mathematics technical team of the State Ministry; furthermore, the teachers claim they are not knowledgeable enough to make a discussion on the subject possible, let alone to teach it.